COMPARISON OF INDONESIAN AND MALAYSIAN STUDENT ENTREPRENEURSHIP STUDIES: A MANAGEMENT AND ACCOUNTING PERSPECTIVE - Vivi Oxana Putri; Marsaulina Sirait; Della Aureliya; Hafizah Khaira Nasution; Ginta Puspita; Etriyani Karolina Br Sembiring; Miftahul Jannah; Eliza Rusliana Br Harahap; Anisa; Annisa Sanny; Ayu Kurnia Sari; Noni Ardi (RADJA PUBLIKA, 2025)
This study aims to compare the implementation of entrepreneurship education at Universitas Pembangunan Panca Budi (UNPAB) Medan, Indonesia, and Universiti Putra Malaysia (UPM) from management and accounting perspectives. The research is based on the importance of entrepreneurship education in preparing graduates with adaptive business skills in the Southeast Asian digital economy era. Theoretical review refers to the concepts of Strategic Management Accounting (SMA) and Management Control Systems (MCS) which support decision-making based on data and business performance indicators. This study used a qualitative method with a case study approach at both universities, involving observation, in-depth interviews, and documentation of student entrepreneurship programs. The findings show that practical-based entrepreneurship education at both institutions significantly improves students’ managerial, accounting, and business skills. Students involved in business incubators, campus bazaars, and small business operations can prepare simple financial reports, analyze operational costs, and determine business strategies based on financial and non-financial data. In conclusion, the entrepreneurship education models developed by UNPAB and UPM effectively shape competent young entrepreneurs, and it is recommended that similar programs be implemented more widely in higher education institutions within the region.